2003
DOI: 10.2188/jea.13.120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Physical Activity in Older People: A Randomized Controlled Trial.

Abstract: Background: Recent randomized controlled trials indicated that exercise training for elderly significantly increased their physical fitness. However, very few studies have examined changes in physical activity after exercise training. The purpose of this study was to investigate whether six-month exercise training for older adults can increase and maintain their physical activity in daily life.Methods: Sixty-two men and women aged 60 to 81 years (mean age 67.1 years), living in communities, were randomly alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 17 publications
1
39
0
5
Order By: Relevance
“…Participants in our study were older than in these studies; therefore, extending the findings to an older population. Several previous studies involving older adults suggested decreased nonexercise physical activity (Meijer et al 1999(Meijer et al , 2000 and/or NEAT (Goran and Poehlman 1992;Morio et al 1998;Colley et al 2010) following exercise intervention, but others reported increased or unchanged nonexercise physical activity (Washburn and Ficker 1999;Fujita et al 2003;Church et al 2009). Our study showed that NEAT and nonexercise physical activity did not change in the overall sample.…”
Section: Discussionmentioning
confidence: 95%
“…Participants in our study were older than in these studies; therefore, extending the findings to an older population. Several previous studies involving older adults suggested decreased nonexercise physical activity (Meijer et al 1999(Meijer et al , 2000 and/or NEAT (Goran and Poehlman 1992;Morio et al 1998;Colley et al 2010) following exercise intervention, but others reported increased or unchanged nonexercise physical activity (Washburn and Ficker 1999;Fujita et al 2003;Church et al 2009). Our study showed that NEAT and nonexercise physical activity did not change in the overall sample.…”
Section: Discussionmentioning
confidence: 95%
“…Значај физичког вежбања у функцији очувања и унапређења здравља, побољшања телесног саставастарих особа потврђен је у многим студијама (Grant, Todd, Aitchison, Kelly, & Stoddart, 2004;Coker, Williams, Kortebein, Sullivan, & Evans, 2009;Bakhtiari et al, 2012;Andersen, Schmidt, Pedersen, Krustrup & Bangsbo, 2016) .Савремен начин живота и рада је такав да је технолошки развој примораo човека да се мање фокусира на физичке активности (Weineck, 2004). Aктиван начин живота и свакодневна физичка активност умереног карактера имају значајан утицај на телесни састав старијих особа (Fujita, Nagatomi, Hozawa, Ohkubo, Sato, Anzai, & Tsuji, 2003), јер редовним физичким вежбањем се смањује ризик од настанка разних обољења (ACSM, 1998). Старије особе имају више физичких или медицинских ограничења у односу на млађе особе, и због тога интензитет вежбања је углавном мањи и количина вежбања опада са старењем (Kallinen, & Markku, 1995;Taunton et al, 1997).…”
Section: уводunclassified
“…Furthermore, improved physical fi tness due to training was clarifi ed to increase and maintain physical activity in daily life of older adults (Fujita, et al, 2003), which will lead to improvement in quality of life.…”
Section: Effects Of Regular Exercise On Vasodilatory Capacity and Vesmentioning
confidence: 99%